Knowledge and practice in early modern English medicine, 1550-1680 - Wear, A. (Andrew), 1946- (Cambridge University Press, 2000)
Annotation This is a major synthesis of the knowledge and practice of early modern English medicine, as expressed in vernacular texts set in their social and cultural contexts. The book vividly maps out some central areas: remedies (and how they were made credible), notions of disease, advice on preventive medicine and on healthy living, and how and why surgeons worked on the body. In particular, two of the most high-profile diseases of the age--the pox and the plague--are discussed in detail, and their treatment analyzed.